2002
DOI: 10.1177/00970002042006007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Extended‐Release Glipizide GITS Compared with Immediate‐Release Glipizide in Patients with Type II Diabetes Mellitus

Abstract: This study was designed to compare the pharmacokinetic and short-term pharmacodynamic profile of extended-release glipizide GITS (Glucotrol XL) given in a dosage of 20 mg once daily with that of immediate-release glipizide (Glucotrol) 10mg twice daily in patients with type II diabetes mellitus. In an open-label, randomized, two-way crossover study, each glipizide formulation was administered for 5 days. Serial blood samples were drawn at baseline and on the 5th day of each treatment phase for measurement of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…Slow release formulations of glipizide and gliclazide result in lower, more sustained concentrations of SUs. For example, standard release glipizide has a statistically higher C max of 1003 ng/mL lasting 1‐8 hour, and may be given twice daily, whereas extended release glipizide has a C max of 499 ng/mL lasting 6‐12 hour . In keeping with our hypothesis that lower dosing of SUs may be beneficial by enabling incretin action with minimal insulin secretion, modified‐release gliclazide or glipizide are associated with low hypoglycaemic risk versus their short‐acting preparations such as glibenclamide/glyburide or glimepiride, or the difference in SU‐associated body weight gain, and faster time‐to‐failure with glibenclamide (C max 97.2‐105 ng/mL after 2 h) than chlorpropamide (C max 22.7‐26.8 ug/mL sustained from 3 hour)…”
Section: Is There a Role For Low‐dose Sulphonylureas?supporting
confidence: 61%
“…Slow release formulations of glipizide and gliclazide result in lower, more sustained concentrations of SUs. For example, standard release glipizide has a statistically higher C max of 1003 ng/mL lasting 1‐8 hour, and may be given twice daily, whereas extended release glipizide has a C max of 499 ng/mL lasting 6‐12 hour . In keeping with our hypothesis that lower dosing of SUs may be beneficial by enabling incretin action with minimal insulin secretion, modified‐release gliclazide or glipizide are associated with low hypoglycaemic risk versus their short‐acting preparations such as glibenclamide/glyburide or glimepiride, or the difference in SU‐associated body weight gain, and faster time‐to‐failure with glibenclamide (C max 97.2‐105 ng/mL after 2 h) than chlorpropamide (C max 22.7‐26.8 ug/mL sustained from 3 hour)…”
Section: Is There a Role For Low‐dose Sulphonylureas?supporting
confidence: 61%
“…Previous studies have shown that glipizide has beneficial effects on glycaemic control, the insulin secretory response and hepatic glucose production 7 . In addition, glipizide CR tablets may reduce the risk of hypoglycaemia 7,27 . However, previous studies did not evaluate the effects of glipizide CR tablets on glucose variability.…”
Section: Discussionmentioning
confidence: 99%
“…These dose-validation studies were conducted under pentobarbital anesthesia, because ketamine-xylazine masks the known glucose lowering effects of sulfonylureas [4]. We showed that a 45-60 min infusion of glipizide provided exposure similar to that observed clinically [20] and caused a 51% increase in plasma insulin. We also determined an infusion dose of glibenclamide that led to plasma concentrations (0.68 µg/mL) similar to those reported in a clinical study (0.48 µg/mL), in which glibenclamide inhibited IPC-induced cardioprotection [21].…”
Section: Discussionmentioning
confidence: 80%
“…The dosing regimen for both drugs was calculated based on pharmacokinetic modeling to achieve steady-state plasma concentrations in anesthetized rabbits. For glipizide, the target (clinically relevant) plasma concentration was 1-2 µg/mL [20], while the glibenclamide infusion dose was based on achieving plasma levels of 0.5-1 µg/mL [21]. After 45 min of infusion, all hearts were preconditioned (IPC) by tightening the coronary artery snare for 5 min of regional ischemia followed by 10 min reperfusion.…”
Section: Dose Setting and Efficacy Studies Under Pentobarbital Anesthmentioning
confidence: 99%